2022
DOI: 10.1177/13623613221117914
|View full text |Cite
|
Sign up to set email alerts
|

‘Autistic person’ or ‘person with autism’? Person-first language preference in Dutch adults with autism and parents

Abstract: The language used to refer to autism has been a topic of ongoing debate. Research in English-speaking countries indicated an overall preference for identity-first language (‘autistic person’) among autistic adults rather than person-first language (‘person with autism’). We examined terminology preference in Dutch autistic adults ( n = 1026; 16–84 years; 57% women) and parents of autistic children ( n = 286) via an online survey. A majority of self-reporting adults with autism (68.3%) and parents (82.5%) demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 19 publications
2
45
0
1
Order By: Relevance
“…Avoiding the language of pathology (e.g., symptoms, comorbidities, high/low functioning) in favour of more neutral alternatives (e.g., characteristics, co-occurring considerations, individual abilities or support needs) is a simple modification that can have a meaningful impact on students’ sense of place in the classroom, and in turn, how the education community of peers and staff make sense of difference ( Bottema-Beutel et al, 2021 ). There is good evidence, at least in the Anglophone world, that many autistic people prefer identity-first language (e.g., autistic student) over person-first language (e.g., student with autism), which can imply that the autism is separable from the person ( Kenny et al, 2015 ; Taboas et al, 2022 ; see Buijsman et al, 2022 for different terminology preferences in a Dutch sample). Analogous identity-first terminology for other neurodevelopmental differences is not yet clear or settled, but the language of neurodiversity is constantly evolving.…”
Section: Contextual Approaches To Neurodiversitymentioning
confidence: 99%
“…Avoiding the language of pathology (e.g., symptoms, comorbidities, high/low functioning) in favour of more neutral alternatives (e.g., characteristics, co-occurring considerations, individual abilities or support needs) is a simple modification that can have a meaningful impact on students’ sense of place in the classroom, and in turn, how the education community of peers and staff make sense of difference ( Bottema-Beutel et al, 2021 ). There is good evidence, at least in the Anglophone world, that many autistic people prefer identity-first language (e.g., autistic student) over person-first language (e.g., student with autism), which can imply that the autism is separable from the person ( Kenny et al, 2015 ; Taboas et al, 2022 ; see Buijsman et al, 2022 for different terminology preferences in a Dutch sample). Analogous identity-first terminology for other neurodevelopmental differences is not yet clear or settled, but the language of neurodiversity is constantly evolving.…”
Section: Contextual Approaches To Neurodiversitymentioning
confidence: 99%
“…Preferred language and terminology in relation to autism and other neurodevelopmental conditions is to some extent culturally determined and continue to evolve [21]. In English-speaking countries, research highlights a preference for "identity first" language and reference to "autistic people," however a review of Dutch people, reported a preference for person first language-referring to "people with autism" [22]. In our own community in Scotland, autistic people have shared with us how important their autistic identity is and how much language matters [23].…”
Section: Language and Mindsets Mattermentioning
confidence: 99%
“…1 There are some exceptions to this, as some patient groups, such as those with autism, have gone on record as saying that they prefer "identity-first" language, although preferences within patient groups may vary by country or language background. 2 The JAMA Network, which publishes the AMA Manual of Style, has also done considerable work to provide guidance to authors on how to appropriately report information about age, race, ethnicity, sex, gender, indigenous status, and other human characteristics that must be carefully described to maintain individuals' dignity and avoid furthering historical inequities. 3 Authors should refer to the guidance on appropriate reporting of demographic information and the use of inclusive language when preparing manuscript submissions.…”
Section: Editorialmentioning
confidence: 99%
“…For example, rather than referring to study participants as “diabetics,” we would say “persons with diabetes.” 1 There are some exceptions to this, as some patient groups, such as those with autism, have gone on record as saying that they prefer “identity-first” language, although preferences within patient groups may vary by country or language background. 2…”
mentioning
confidence: 99%